2018
DOI: 10.1007/s11367-018-1503-3
|View full text |Cite
|
Sign up to set email alerts
|

A scalable life cycle inventory of an automotive power electronic inverter unit—part I: design and composition

Abstract: Purpose A scalable life cycle inventory (LCI) model, which provides mass composition and manufacturing data for a power electronic inverter unit intended for controlling electric vehicle propulsion motors, was developed. The purpose is to fill existing data gaps for life cycle assessment (LCA) of electric vehicles. The model comprises new and easy-to-use data with sufficient level of detail to enable proper component scaling and more in-depth analysis of inverter units. It represents a stand-alone three-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…These parameters are those that are identified to be of high importance to the inventories, as shown in Figure 1. Parameterization allows multiple variants of a base inventory model to be generated by varying key parameters or levers, which are usually external to the unit processes [64][65][66][67]. By doing so, we can assess the effect of parameter variation on the overall footprints of the value chains investigated.…”
Section: Model Descriptionmentioning
confidence: 99%
“…These parameters are those that are identified to be of high importance to the inventories, as shown in Figure 1. Parameterization allows multiple variants of a base inventory model to be generated by varying key parameters or levers, which are usually external to the unit processes [64][65][66][67]. By doing so, we can assess the effect of parameter variation on the overall footprints of the value chains investigated.…”
Section: Model Descriptionmentioning
confidence: 99%
“…It should be noted that a method can occur in more than one subcategory. For example, Caduff et al use power laws based on empirically observed scaling relationships to scale windmills [35] and heating devices [36] which are both mature products, while similar approaches are applied to model the scale up from lab to industrial size [37,38]. Also, often several methods are combined per study.…”
Section: Framework For Ex-ante Lcamentioning
confidence: 99%
“…Food products - [54] Ethanol production from wheat straw 3-4 [55] Chlor-alkali electrolysis 3-4 - [56] Fullerene and carbon nanotubes 3-4 [57] Ethylene production from wood 7-8 [58] Membrane filtration system 3-4 [59] Antibacterial T-shirt 5 [11] Energy system 9+ [24] Wastewater treatment 5 [38] Power electronic inverter 9+ [37] Power electronic inverter 9+ [60] agriculture [61] But-1,3-diene 3-4 [62] Renewable energy technologies 9+ [63] Liquid phase batch reactions 3-4 + --n.s. [64] Self-cleaning coated float glass 4-5 [65] PV panels [66] Recycling CdTe PV [67] Caprolactam production 2 [68] Scale up of a generic plant 6-7 [69] Scale up of a generic plant 7-8 [70] LFP-CnF batteries 3-4 [29] Transport systems 9+ [17] Cellulose nanocrystal foam 3 and 4 [71] Bio-based plastics 3 [73] Electricity production 9+ - [74] Metal recovery from e-waste 2-3 [75] Metal recovery from e-waste 2-3 [27] Nanosilver T-shirts 3-4 and6-7 [26,76] PV panels 9+ [77] Ethylene production 4-6 - [78] Electric vehicles 9+ -…”
Section: Framework For Ex-ante Lcamentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the calculations can be found in the appendix. For the mounting of the PCB, we use input and output data from [87].…”
Section: Printed Circuit Board (Pcb) Driver Board Logic Board and Bus...mentioning
confidence: 99%